A research study of no fault found (NFF) in the Royal Air Force - Hockley, Chris; Lacey, Laura J. (Elsevier, 2017)
The No Fault Found (NFF) problem continues to reduce operational availability and have an impact on cost and resources in the RAF. Following extensive research by the Centre for Innovative Manufacturing in Through-Life Engineering Services, access was provided to a significant number of RAF aircraft maintenance personnel under the sponsorship of Air Command at RAF High Wycombe. Maintenance personnel from seven different aircraft fleets, including large aircraft, fast jets and rotary platforms were involved. A number of substantial conclusions were made resulting in 26 recommendations. The paper reviews and substantiates these conclusions and recommendations.
Keywords: No Fault Found; maintenance; aircraft; repeat arisings; rogue; fault reporting